Overconfidence Bias Sebagai Penguat Manajemen Koperasi di Kabupaten Lombok Timur - Yusma, Lalu Nova Saza; H, Hilmiyatun (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the advantages of behavioral finance in strengthening cooperative management, particularly through the application of the Overconfidence Bias indicator. The core issues addressed in this research include inefficiencies in financial management, membership administration, and decision-making processes influenced by managerial behavior. A qualitative descriptive approach was employed, with data collected through in-depth interviews involving key and supporting informants. The findings reveal that cooperative managers often overlook the feasibility of creditworthiness when granting loans. However, Mandiri Selong Cooperative has successfully applied behavioral finance principles, particularly in managing Overconfidence Bias, thereby enhancing its management system. This research recommends the adoption of standardized behavioral finance-based management practices by other cooperatives to improve organizational governance and promote sustainable development.